2020
DOI: 10.30880/ijie.2020.12.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption Pattern of Residential Buildings: Case Study of Residential Area in Batu Pahat, Johor

Abstract: According to the National Energy Balance report released by the Energy Commission of Malaysia in 2016, the residential sector uses 21.6% of the total energy in Malaysia. Residents waste energy through inefficient energy consumption and a lack of awareness. Building occupants are considered the main factor that influences energy consumption in buildings, and to change energy consumption on an overall scale, it is crucial to change individual behaviour. Therefore, this study focused on analysing the energy consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Regarding household energy consumption, previous studies have shown that the use of home appliances, especially the use of ACs, significantly contributes to the increase in household energy consumption in tropical regions [10][11][12][13][14][15]. For instance, Batih et al [10] investigated household electric consumption in the urban households of Indonesia through a bottom-up estimation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding household energy consumption, previous studies have shown that the use of home appliances, especially the use of ACs, significantly contributes to the increase in household energy consumption in tropical regions [10][11][12][13][14][15]. For instance, Batih et al [10] investigated household electric consumption in the urban households of Indonesia through a bottom-up estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there are a few reports that have investigated the effectiveness of energy conservation measures in the residential buildings of tropical regions [10][11][12][13][14]19,20,[30][31][32]. However, very few have focused on collective housing exclusively.…”
Section: Introductionmentioning
confidence: 99%